IDENTIFIKASI PENGARUH GELOMBANG DAN BUNYI PADA FENOMENA MENDENGAR - Sihotang, Hartati Kartika Br; Karo, Judha Stepanus; Sihotang, Kartini Anggi Agata; Simbolon, Vipta Niva Mariana; Lubis, Rajo Hasim (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2024)
Waves are vibrations that propagate, either through the media or not through the media. Sound is wave energy that comes from a sound source, namely a vibrating object. Where the purpose of this study is to find out how waves and sound affect the phenomenon of hearing. Based on the problems raised, the research method that is suitable for use is in the form of literature studies or literature studies. Literature study can be reached by collecting references consisting of several previous studies which are then compiled to draw conclusions. The sound that the human ear hears changes from a mechanical acoustic signal to an electrical signal that is passed on by the auditory nerve to the brain. The results showed that the process of hearing goes through three stages, namely the stage of transferring physical energy in the form of a sound stimulus to the hearing organ, the conversion or transduction stage, namely the conversion of the physical energy stimulation to the receiving organ and the stage of transmitting nerve impulses to the auditory cortex and of course it cannot be separated from the human hearing organ. namely ears. The process of hearing is a process that is not simple, in order to hear humans must have good hearing organs and hearing function. The organ system of hearing is divided into peripheral and central.